Analysis of the Implementation of the Independent Curriculum in the Bina Insani Integrated Islamic Elementary School in Semarang City - Hengki Firman Syah; Sri Wardani; Tri Suminar (Innovative Journal of Curriculum and Educational Technology, 2023)
In order to recover after the pandemic COVID 19, the Indonesian government issued a curriculum change policy. My study aims to find out and understand the readiness of the implementation of the Independent Curriculum at Bina Insani Integrated Islamic Elementary School which is carried out by the principal, teachers and students. The implementation of the Independent Curriculum at Bina Insani Integrated Islamic Elementary School which is carried out by the principal, teachers and students, the outcomes of student learning class I and IV is in the form of learning outcomes and Pancasila Student Profiles on the implementation of the Independent Curriculum at Bina Insani Integrated Islamic Elementary School, and obstacles and solutions in implementing the Independent Curriculum at the Integrated Islamic Elementary School Bina Insani Semarang. This study uses a qualitative research method with a case study approach. Data collection techniques, namely observing school conditions and learning activities, interviewing the implementation of the independent curriculum, documentation studies. Data analysis techniques by examining all available data from various sources, data reduction, compiling reduced data, presenting data, and checking data validity. Based on the results of this study, the planning stage begins with accepting regulations from the government, establishing the school's vision, mission, and goals, preparing KOSP Bina Insani Integrated Islamic Elementary School, planning lessons, planning P5 activities. At the implementation stage of the curriculum, there are still some that have not been optimally implemented, such as learning activities that still need the teacher's understanding in differentiated learning. At the stage of evaluating the implementation of Bina Insani Integrated Islamic Elementary School which was carried out by the teacher, he had carried out a diagnostic to summative assessment. The results of this study can be used to add insight into the implementation of the independent curriculum in the learning process carried out by all components in schools using the independent curriculum .